Biocompatible conjugation for biodegradable hydrogels as drug and cell scaffolds. Issue 1 (1st January 2020) - Fan, Ming; Tan, Huaping
Abstract: Biodegradable and biocompatible hydrogels have many different applications in the field of biomedicine. The hydrogels could be utilized as drug carriers and cell scaffolds for drug delivery and tissue engineering. The hydrogels are appealing scaffolds because they are structurally similar to the extracellular matrix (ECM) of many tissues, which can often be delivered in a minimally invasive manner. A major issue in the use of a hydrogel scaffold is that the establishment of a biomimic environment is necessary for engineered tissue survival. In tissue engineering, there is significant interest in exploiting biocompatible conjugation to construct mimics of ECM for cells culture applications. Recently, a variety of crosslinking strategies have been developed for the fabrication of hydrogels, which are based on an affinity interaction, ionic interaction, electrostatic interaction, hydrophobic interaction, hydrogen bonding, crystallinity and covalent conjugation. This review will discuss recent advances in the field of biodegradable hydrogels crosslinked via biocompatible conjugation, including both physical and covalent crosslinking, which can be potentially used as drug and cell scaffolds in regenerative medicine applications.